Sport-specific impacts on pulmonary function: a comparative analysis of swimmers and long-distance runners - Ikhsan, Faihanah; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Adnan, Aizzat; Linoby, Adam; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study compares pulmonary function metrics, including FVC, FEV1, and PEF, between trained swimmers and long-distance runners to investigate how different training environments and respiratory demands drive sport-specific physiological adaptations. By analyzing these variables, the research seeks to clarify the impact of water versus land-based endurance training on lung capacity and respiratory efficiency. Ultimately, the findings contribute to a deeper understanding of respiratory physiology to help optimize specialized endurance training programs for elite athletes